The Fire Resistance of Monolithic Floor Slabs of Buildings and for Various Exposure Areas of the Fire - K. Ksenofontova, T.; ., . (International Journal of Engineering and Technology, 2018)
Structural design of buildings is currently performed on operational loads without taking into account the possible impact of fire. However, as practice has shown, fires often occur in both residential and public buildings. In this case, there is a strong heating of the supporting structures, due to which there is a change in their mechanical properties, and they behave differently from the design loads before the fire. The article considers the impact of fire on the internal forces and deflections of monolithic slabs of buildings.Â Â